Seeking and experiencing meaning: Exploring the role of meaning in promoting mental adjustment and eudaimonic well-being in cancer patients. Issue 3 (14th May 2014) - Scrignaro, Marta; Bianchi, Elisabetta; Brunelli, Cinzia; Miccinesi, Guido; Ripamonti, Carla Ida; Magrin, Maria Elena; Borreani, Claudia
Abstract: Objective: The present study is the result of theory-driven research investigating the role of the search for and presence of meaning in enhancing both mental adjustment and eudaimonic well-being in cancer patients. Method: A cross-sectional study involved 266 cancer patients currently in the treatment and management phase of their illness. Data were collected by a written questionnaire. The search for meaning was assessed with the Seeking of Noetic Goals Test, and the presence of meaning was assessed using the Purpose in Life Test. Mental adjustment to a cancer diagnosis was assessed by two subscales of the Italian version of the Mini-Mental Adjustment to Cancer Scale, and eudaimonic well-being was assessed with the Psychological Well-Being Scale. Correlation and mediation analyses based on five thousand bootstrapping samples were performed. Results: The mediation analyses showed that the presence of meaning totally or partially mediated the effect of the search for meaning on both mental adjustment and eudaimonic well-being. Further correlation analyses showed a high negative correlation between eudaimonic well-being and hopelessness. Significance of results: Our results appear relevant from both the theoretical and clinical points of view. They support a deeper understanding of the combined contribution of the search for and presence of meaning in promoting well-being in cancer patients. Simultaneously, they are consistent with suggestions from recent studies on the clinical psychology of posttraumatic growth and emphasize the relevance of eudaimonic well-being as a protective factor for hopelessness.